Etika Kerja Aparatur Pemerintah Desa Lantapan Kecamatan Galang Kabupaten Tolitoli - Marlina (PT FORMOSA CENDEKIA GLOBAL, 2022)
Village Government Apparatus Work Ethics is the attitude or work behavior of village officials in carrying out their duties and authorities in providing public services. The purpose of this study was to find out how the work ethic of the Lantapan village government apparatus, Galang District, Tolitoli Regency. This research was carried out at the Lantapan Village office, Galang District, Tolitoli Regency. In this study using a qualitative descriptive method. Data collection techniques using observation, interviews and documentation. The 10 informants in this study were conducted using purposive sampling technique. The results of this study by referring to the work ethic theory of Ahmad Janan Asifudin have not been maximized even though there have been rules that have been applied because of the five indicators there are only indicators that are adequate even though the application is not too optimal.